Decision Support System untuk Menentukan Lokasi Cabang Baru Muhri Fashion Menggunakan Penggabungan TOPSIS dan SAW - Winda Pertiwi; Nurahman Nurahman; Abdul Aziz (STMIK Budi Darma, 2022)
Business is a commercial field of business that is in great demand. One of them is a business in the field of fashion or fashion. Fashion or fashion is something that is in demand by the wider community with an attraction to the way, pattern, and even decoration in the form of clothing, levis, trousers, and other fashions. The owner of the Haji Muhri shop is one of the people who are interested in doing business in the fashion world. The shop owner will set up a new store branch in the East Kotawaringin area, Central Kalimantan. The researcher offers owners to use a combination of the Simple Additive Weighting (SAW) method and the Technique For Order Preference By Similarity To Ideal Solution (TOPSIS), as a decision support system. Decision support system is a system that has the ability to perform an analysis of the decision-making model. Decision support system (DSS) is also a system with alternative processes that have a specific purpose, meaning that this system can be used in situations that are even very rare. The combination of methods between SAW and TOPSIS serves to produce an optimal decision based on alternatives and predetermined criteria. This study uses 7 locations as alternatives and 9 criteria. In this study, the alternative locations chosen were Mentawa Baru Hulu, Mentawa Baru Hilir, Ketapang, Sawahan, Baamang Hulu, Baamang Tengah, and Baamang Hilir, which resulted in Mentawa Baru Hilir with a value of 0.751 or 75.1% as the highest value from the location. other calculations that have been made to be the best alternative for the location of the new branch of the Haji Muhri Fashion Store